Pengaruh Pemasaran Syariah, Kualitas Produk, Dan Harga Terhadap Keputusan Pembelian Di Tiktok Shop Pada Generasi Z Di Jepara - Khoirondi, Ahmad; Sa'diyah, Mahmudatus (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2025)
The rapid development of e-commerce and social media has changed the landscape of consumer behavior, particularly among Generation Z. TikTok Shop is emerging as a significant platform in influencing purchasing decisions through creative and interactive content. In this context, sharia marketing is an important aspect, as awareness of Islamic values in consumption increases. This study aims to find out the TikTok Shop purchase decision in generation Z in Jepara which is influenced by sharia marketing, product quality, and price. The population in this study is Generation Z who use the TikTok Shop application in Jepara. Sampling was done using the purposive sampling method, with a sample of 100 respondents. The method used in the study is in the form of a quantitative method with multiple linear regression analysis through SPSS software version 30. The type of data in this study is from primary data, using a questionnaire. This study found that Sharia Marketing does not have a significant influence on purchase decisions, product quality has a significant influence on purchase decisions, and Price has a significant influence on purchase decisions. These findings confirm that the integration of sharia values in digital marketing strategies can increase product attractiveness among Generation Z. In addition, maintaining product quality and price remains crucial in maintaining consumer loyalty. The practical implication of this study is the need for business people to adopt a marketing approach that is in line with sharia principles and focus on improving product quality to meet the expectations of generation z consumers in Jepara who are increasingly selective.